DO ADJUSTING-AMOUNT AND ADJUSTING-DELAY PROCEDURES PRODUCE EQUIVALENT ESTIMATES OF SUBJECTIVE VALUE IN PIGEONS? - Green, Leonard; Myerson, Joel; Shah, Anuj K.; Estle, Sara J.; Holt, Daniel D. (Journal of the experimental analysis of behavior, 2007)
The current experiment examined whether adjusting‐amount and adjusting‐delay procedures provide equivalent measures of discounting. Pigeons' discounting on the two procedures was compared using a within‐subject yoking technique in which the indifference point (number of pellets or time until reinforcement) obtained with one procedure determined the value of the corresponding variable in the yoked condition with the other procedure. Behavior on each procedure was well described by a hyperbolic discounting function. Results revealed no systematic differences in the degree of discounting as measured by the discounting rate parameter of the hyperbola in Experiment 1, which used 20‐mg pellets. These results were replicated in Experiment 2 using smaller, 14‐mg pellets, which potentially yield more precise measurement of indifference points on the adjusting‐amount procedure. The finding that estimates of the k parameter in the hyperbolic discounting function obtained with one procedure did not differ systematically from estimates obtained from the same subjects with the other procedure represents strong support for the hypothesis that the same process underlies the discounting of delayed rewards on both adjusting‐amount and adjusting‐delay procedures.